Exosomes genetic cargo in lung cancer: a truly Pandora’s box - Pablo Reclusa; Rafael Sirera; António Araújo; Marco Giallombardo; Anna Valentino; Laure Sorber; Ignacio Gil‐Bazo; Patrick Pauwels; Christian Rolfo (2016)
Abstract: Lung cancer is a highly lethal disease. Targeted therapies have been developed in last years, however survival rates are not improving due to the delay in the diagnosis, making biomarkers one of the most interesting fields of study in cancer. Liquid biopsy has raised as an alternative to tissue biopsy due to improvements in analytical techniques for circulating tumor cells (CTCs), cell free DNA and exosomes. Among all, exosomes have raised as one of the most promising tools to understand the tumor due to their stability in the blood and their similarity to the cells of origin. In the last years, different alterations have been described inside the exosomes derived from non-small cell lung cancer (NSCLC) cells mirroring the processes inside these tumoral cells, such as EGFR mutation, translocations or microRNA (miRNA) deregulation. All these studies have opened the window to a new world of possibilities in the study of tumor biomarkers.